Progress of brown rust and orange rust of sugarcane in Cuba - Osmany de la Caridad Aday-Díaz (Universidad Central "Marta Abreu" de Las Villas, 2021)
In Cuba, sugarcane brown rust (Puccinia melanocephala) is one of the most important diseases and orange rust (Puccinia kuehnii) is considered a potentially dangerous disease. The objectives of the present investigation were: to quantify the development of brown and orange rust; to determine the influence of the planting time and age of the plants on the severity of these diseases; and the period in which the levels of both rusts are the highest. It was found that the months of planting have a very similar influence on the manifestation of the symptoms of both rusts with greater affectation in the plantations that were carried out from July to December and in the month of April. The severity of brown rust was significantly higher from three to five months of age after planting, however, in orange rust the severity remained above the average observed until seven months. The severity of orange rust increased with the age of the plants in the plantations that were carried out from January to April. Unlike brown rust, regardless of the age of the plants, the severity of orange rust can be increased when favorable environmental conditions exist.